KONVERGENSI MEDIA SURAT KABAR LOKAL (Studi Deskriptif Pemanfaatan Internet Pada Koran Tribun Jogja dalam Membangun Industri Media Cetak Lokal) - Khadziq Khadziq (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Media competition and the development of Information and Communication Technology (ICT), which brings a new trend in the world of the communications industry. Instrument to deal with it is the convergence oriented to the interests of consumers and media owners. Media who had converged also affect the amount of economic and political interests in the application of convergence. Data collection is done by observation and in-depth interviews and review of the literature. Descriptive analysis showed that the strategy of 3M (Multimedia, Multichannel and Multiplatform) used Tribun Jogja be one alternative strategy for implementing the convergence and transforming itself towards full convergence.While in political economy it is seen that through the application of media convergence, then the commodification that is their decision and uniformity of content among media that are under the network Tribune will benefit through the supply of advertisers, as well as spatialization that enables the distribution of news content in real time can reduce labor costs, administrative and material. The conclusion from this study is that convergence is the convergence contextual done that convergence is tailored to the needs and conditions of the corporate culture and society. It proved convergence can be accomplished without a radical change by uniting print and online newsrooms, media have to do convergence. Keywords: media convergence, Continuum Convergence, the media and political economy, Tribun Jogja Newspaper.